Efficacy of melatonin, IL-25 and siIL-17B in tumorigenesis-associated properties of breast cancer cell lines - Gelaleti, Gabriela Bottaro [UNESP]; Borin, Thaiz Ferraz; Maschio-Signorini, Larissa Bazela; Moschetta, Marina Gobbe; Jardim-Perassi, Bruna Victorasso; Calvinho, Guilherme Berto; Facchini, Mariana Castilho; Viloria-Petit, Alicia M.; de Campos Zuccari, Debora Aparecida Pires [UNESP] (Elsevier, 2017)
Mammary tumorigenesis can be modulated by melatonin, which has oncostatic action mediated by multiple mechanisms, including the inhibition of the activity of transcription factors such as NF-κB and modulation of interleukins (ILs) expression. IL-25 is an active cytokine that induces apoptosis in tumor cells due to differential expression of its receptor (IL-17RB). IL-17B competes with IL-25 for binding to IL-17RB in tumor cells, promoting tumorigenesis. This study purpose is to address the possibility of engaging IL-25/IL-17RB signaling to enhance the effect of melatonin on breast cancer cells. Breast cancer cell lines were cultured monolayers and 3D structures and treated with melatonin, IL-25, siIL-17B, each alone or in combination. Cell viability, gene and protein expression of caspase-3, cleaved caspase-3 and VEGF-A were performed by qPCR and immunofluorescence. In addition, an apoptosis membrane array was performed in metastatic cells. Treatments with melatonin and IL-25 significantly reduced tumor cells viability at 1 mM and 1 ng/mL, respectively, but did not alter cell viability of a non-tumorigenic epithelial cell line (MCF-10A). All treatments, alone and combined, significantly increased cleaved caspase-3 in tumor cells grown as monolayers and 3D structures (p < 0.05). Semi-quantitative analysis of apoptosis pathway proteins showed an increase of CYTO-C, DR6, IGFBP-3, IGFBP-5, IGFPB-6, IGF-1, IGF-1R, Livin, P21, P53, TNFRII, XIAP and hTRA proteins and reduction of caspase-3 (p < 0.05) after melatonin treatment. All treatments reduced VEGF-A protein expression in tumor cells (p < 0.05). Our results suggest therapeutic potential, with oncostatic effectiveness, pro-apoptotic and anti-angiogenic properties for melatonin and IL-25-driven signaling in breast cancer cells.
Keywords: Apoptosis; Breast cancer; Interleukin-17B; Interleukin-17E; Interleukin-25; Melatonin; VEGF